2015
DOI: 10.1007/s40266-015-0296-3
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of Antihypertensive Medications in Older Adults

Abstract: Several guidelines for hypertension have recently undergone revisions to incorporate an approach providing choices of medications based on age, race, and specific situations where hypertension may co-exist with disorders such as diabetes, coronary artery disease, heart failure and chronic kidney disease. Initial recommendations include diuretics, angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and calcium channel blockers; beta blockers are favored in some guidelines and are a choice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 183 publications
1
9
0
2
Order By: Relevance
“…Based on small controlled trials and clinical experiences angiotensin converting enzyme inhibitor, thiazides, calcium channel blockers, and statins turned to be useful in treating obesity-related hypertension [20]. However, these drugs draw adverse effects including tolerability [21], renal dysfunction [22], angina, arrhythmias, hypotension, arthritis, asthma etc. [23].…”
Section: Discussionmentioning
confidence: 99%
“…Based on small controlled trials and clinical experiences angiotensin converting enzyme inhibitor, thiazides, calcium channel blockers, and statins turned to be useful in treating obesity-related hypertension [20]. However, these drugs draw adverse effects including tolerability [21], renal dysfunction [22], angina, arrhythmias, hypotension, arthritis, asthma etc. [23].…”
Section: Discussionmentioning
confidence: 99%
“…Using beta blockers in psychiatry involves a lot of controversy. There is certain evidence supporting the use of beta blockers in treating panic disorder and PTSD; however, it is not recommended to apply them in the treatment of other forms of anxiety [83]. It was demonstrated in a number of casuistic works that metoprolol can cause anxiety in elderly patients, which is relieved or subsides after the drug is discontinued [84].…”
Section: Risk Factors Related To Using Adrenolytic Drugs In the Pharmmentioning
confidence: 99%
“…Zastosowanie beta-blokerów w psychiatrii niesie ze sobą wiele kontrowersji. Istnieją pewne dowody popierające stosowanie beta-blokerów w leczeniu lęku panicznego oraz PTSD, jednak wdrażanie ich nie jest wskazane w leczeniu innych form lęku [83]. W kilku pracach kazuistycznych wykazano, że metoprolol może wywoływać lęk u pacjentów w podeszłym wieku, który łagodzi się lub ustępuje po odstawieniu leku [84].…”
Section: Czynniki Ryzyka Związane Ze Stosowaniem Adrenolityków W Farmunclassified
“…While there is evidence to support the use of beta-blockers to treat performance anxiety, their use is inot indicated to treat other forms of anxiety [74]. Several case studies have shown metoprolol may induce anxiety in elderly patients, which improves or resolves with discontinuation of the drug [75].…”
Section: Beta-blockersmentioning
confidence: 99%